The Influence Of Profitability, Liquidity And Leverage On Company Value With Dividend Policy As A Moderating Variable In Raw Goods Sector Companies Listed On The Indonesian Stock Exchange In 2017–2021 - Dwi Hanny Khairunissa; Zuwina Miraza; Hafriz Rifki Hafas (Sean Institute, 2025)
This study aims to identify and analyze the effect of profitability, liquidity, and leverage on the value of raw material sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. In addition, this study also aims to see whether dividend policy is able to moderate the relationship between these independent variables and firm value. This study provides an overview of how the financial condition of companies in the sector is related to the dividend policy taken, as well as how factors such as profitability, liquidity, and leverage affect firm value, both directly and in the context of interactions with dividend policy. The results of the study indicate that profitability and liquidity have a significant positive effect on firm value, while leverage does not have a significant effect and tends to be negative. Dividend policy acts as a moderator that strengthens the effect of profitability on firm value, but weakens the effect of liquidity and leverage. These findings demonstrate the importance of dividend policy in moderating the relationship between a company's financial condition and firm value, and highlight the need for management to consider the right dividend policy in an effort to increase firm value, especially in the raw material sector listed on the IDX.